1988
DOI: 10.1246/bcsj.61.3637
|View full text |Cite
|
Sign up to set email alerts
|

General Reactivity of 2-Lithiobenzothiazole to Various Electrophiles and the Use as a Formyl Anion Equivalent in the Synthesis of α-Hydroxy Carbonyl Compounds

Abstract: The reaction of 2-lithiobenzothiazole with a variety of electrophiles such as aldehydes, ketones, carboxylic esters, lactones, nitriles, and amides afforded the expected addition and substitution products. Trimethylsilyl chloride readily reacted with the benzothiazolyl anion to give 2-trimethylsilylbenzothiazole, while common alkyl halides including primary iodide and benzyl halides, as well as epoxides, did not react with the anion. This characteristic nucleophilicity of the anion was also demonstrated by its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…In line with this observation, Itoh and co-workers reported that the C2-lithiated benzothiazole (Li-1 A) is very unstable even at À50 8C. [26] To evaluate whether the deprotonation is taking place during nickel catalysis, we conducted the coupling in the presence of tBuOD (Scheme 5). When 1 A (1.5 equiv) was treated with 2 a (1.0 equiv), NiA C H T U N G T R E N N U N G (OAc) 2 (10 mol %), bipy (10 mol %), LiOtBu (2.0 equiv), and tBuOD (2.0 equiv), in 1,4-dioxane at 120 8C for 10 h, 42 % of recovered 1 A was deuterated at the C2 position (coupling product 3 Aa was formed in 44 % yield).…”
Section: Introductionmentioning
confidence: 65%
“…In line with this observation, Itoh and co-workers reported that the C2-lithiated benzothiazole (Li-1 A) is very unstable even at À50 8C. [26] To evaluate whether the deprotonation is taking place during nickel catalysis, we conducted the coupling in the presence of tBuOD (Scheme 5). When 1 A (1.5 equiv) was treated with 2 a (1.0 equiv), NiA C H T U N G T R E N N U N G (OAc) 2 (10 mol %), bipy (10 mol %), LiOtBu (2.0 equiv), and tBuOD (2.0 equiv), in 1,4-dioxane at 120 8C for 10 h, 42 % of recovered 1 A was deuterated at the C2 position (coupling product 3 Aa was formed in 44 % yield).…”
Section: Introductionmentioning
confidence: 65%
“…Then nucleophilic addition [67] of 5iiia (after in situ lithiation in the 2-position) to 5iiib in THF at −15°C for 90 minutes yielded the secondary alcohol 5ii . The latter was oxidized to the carbonyl derivative 5i using stabilized 2-iodoxybenzoic acid (SIBX) as oxidative reagent in THF at 60°C [68] prior to the removal of both silyl protecting groups under mild basic conditions (TBAF in THF at room temperature for 2 hours) [69] to afford compound 5 .…”
Section: Methodsmentioning
confidence: 99%
“…15 Encouraged by a report that 2-lithiobenzothiazole undergoes single addition to esters due to the formation of a stable tetrahedral intermediate, 16 we anticipated that heterocyclic aromatic ketone analogs may be prepared directly from methyl rocaglate (Chart 3). Indeed, 2-lithiobenzothiazole (3.1 equiv) was prepared and reacted with methyl rocaglate at -78 °C for 1 h to yield the desired benzothia-zole ketone 25 in 50% yield based on recovered starting material (BRSM).…”
mentioning
confidence: 99%